Immunogenicity analysis of a composition of inactivated human rotavirus A strains in mice following immunisation - M. V. Kovrizhko; E. P. Kolpakova; D. S. Kolpakov; T. I. Tverdokhlebova; E. S. Kurbatov (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODUCTION. Currently, rotavirus infection is prevented with live attenuated vaccines. However, international and Russian vaccination practices, as well as the physiological characteristics of paediatric patients, necessitate the development of inactivated rotavirus vaccines. Prerequisites for the development of such vaccines are the availability of virus strains capable of stable replication and the selection of optimal inactivation conditions providing for the required antigenicity and immunogenicity levels.AIM. This study aimed to evaluate and compare the characteristics of the rotavirus-specific immune response to native strains and to a composition of inactivated rotavirus A strains in a mouse model.MATERIALS AND METHODS. The study used human rotavirus A strains (RRV-4, RRV-5, RRV-6, and RRV-7), a standard rotavirus strain (SA-11 NVC 2364, National Virus Collection of the Russian Federation), and cultures of pig embryo kidney cells treated with Versene solution (SPEV) and Vero cells. Virus titration was used to determine the infectivity of the strains grown in Vero cells maintained in continuous culture. The authors monitored infected cell cultures up to the onset of the cytopathic effect, calculated the 50% tissue culture infectious dose (TCID50) by the Kärber method modified by Ashmarin, and expressed the results as log10 TCID50/mL. Virus strains were inactivated with formaldehyde. To evaluate immunogenicity, outbred white mice were immunised with native strains and the composition of inactivated strains (RRV-4, RRV-5, RRV-6, and RRV-7). After immunisation, blood was taken from the animals, and the serum titre of rotavirus A antibodies was determined by indirect heterogeneous enzyme immunoassay.RESULTS. The infectivity of the rotavirus strains adapted to Vero cells ranged from 8.9 to 7.9 log10 TCID50/mL. When selecting inactivation conditions, the authors showed that inactivation occurred at a temperature of 37 °C and a formaldehyde concentration of 0.05–0.025% (depending on the duration of treatment). The antigenicity analysis demonstrated that the antigen titre of the inactivated strain composition (1:16) was lower than that of native strains (1:32–1:64). The authors demonstrated comparability of immunogenicity profiles of the inactivated strain composition and native strains in mice.CONCLUSIONS. The study generated candidate rotavirus A strains that exhibited stable replication in continuous cultures of Vero cells. The authors selected optimal inactivation conditions for these rotavirus strains and developed an inactivated strain composition showing antigenicity and immunogenicity. The presented data suggest that the composition of inactivated rotavirus A strains can be considered as a basis for further development of an inactivated rotavirus vaccine.